Peran Pendidikan Moral Untuk Mengurangi Aksi Kekerasan Komunikasi di SD Negeri Kertabesuki 01 - Aenun Mudrikah; Didik Tri Setiyoko; Moh Toharudin (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research aims to be able to find out about the study of communication violence in the study of moral education in SD Negeri Kertabesuki 01. This research uses qualitative research by using case studies with data collection techniques using observation, interviews and documentation. Data validity can be done by triangulation. Data analysis techniques that used is data reduction, data presentation, and drawing conclusions. Based on the results of the research, it was concluded that in the cultivation of moral education, it is very important because it can be known the impact of communication violence, including psychological trauma, fear, insecurity, revenge, decreased enthusiasm for learning, concentration power , creativity, loss of initiative, as well as students' (mental) endurance, decreased self-confidence, inferiority, stress, depression, etc. in the long term, this impact can be seen from a decrease in achievement, persistent behavioral changes, therefore for students who experience such actions, immediately share with parents or teachers or people who can be trusted about the violence they experienced so that the student immediately gets help to recover from the condition physical and psychological. Therefore, it is very important for all parties, both teachers, parents and students to understand that violence is not the right solution or action, but rather increases the problem.